Fostering Critical Thinking and Communication Skills In Students: The Foundation For Lifelong Learning - I, Imelda; N, Nadella; Nadia, Nafisah; Harahap, Salsabila; Amirul, Bani (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The purpose of this study is to identify students’ perception towards English speaking ability. The researcher  used  descriptive  qualitative  research  as  the  method  in  this  study. The  Observation  and interview wereused as the instrument. To increase the validity of the data, field note was used to support  the  methodology  of  the  research.  After  analyzing  the  data,  the  researcher  found  thatthe students’ perception toward English speaking ability is various. They realizedthat  speaking  is  an important  skill  in  English  to  be  mastered  well.  They  argued  that  speaking  is  important  skill  to communicate  each  other  especially  as  the  International  and  global  language  used  in  the  world. Unfortunately,  most  of  them  could  not  speak  English  well  and  fluently,  and  many  students  also considered  that  speaking  is  difficult  to  be  mastered  because  of  some  aspects  such  as  limited vocabulary,  less  understanding  of  grammar  and  also  the  pronunciation  which  cannot  be  well.  The  result  also  showed  that  there  are  some  themes  drawn  from  the  interview,  namely students’ difficulties, students’ expectation and need of teacher’s assistance